2009
DOI: 10.3390/medicina45050047
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of photodynamic tumor therapy effectiveness by electroporation in vitro

Abstract: Summary. The aim of our study was to determine if electroporation could improve the effi-Medicina (Kaunas) 2009; 45(5) Correspondence to J.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…The electro-photodynamic therapy applied to lung cancer cells (A549) revealed a significant increase of the cytotoxic effect on cells when compared to HpD-PDT alone, even at drug doses significantly lower than typical levels. The results also demonstrated that the drug was delivered within minutes, instead of hours as in standard PDT (Skolucka et al 2011). Labanauskiene et al (2009 examined Chinese hamster lung fibroblast cell line (DC-3F) (2007) and murine hepatoma MH22A cells.…”
Section: Discussionmentioning
confidence: 54%
“…The electro-photodynamic therapy applied to lung cancer cells (A549) revealed a significant increase of the cytotoxic effect on cells when compared to HpD-PDT alone, even at drug doses significantly lower than typical levels. The results also demonstrated that the drug was delivered within minutes, instead of hours as in standard PDT (Skolucka et al 2011). Labanauskiene et al (2009 examined Chinese hamster lung fibroblast cell line (DC-3F) (2007) and murine hepatoma MH22A cells.…”
Section: Discussionmentioning
confidence: 54%
“…Soon after acknowledging of electroporation as a tool for targeted molecule delivery, it was exploited for intracellular transfer of anticancer drugs and DNA (Kinosita and Tsong 1978;Neumann et al 1982;Mir et al 1988;Labanauskiene et al 2009;Vásquez et al 2012). The feasibility of electroporation to enhance delivery of anticancer drugs into cells and tissues made possible the development of antitumor electrochemotherapy (ECT) , lately optimized in in vivo studies (Serša et al 1995;Miklavčič et al 1998;Š atkauskas et al 2005;Soden et al 2006;Corovic et al 2008;Labanauskien_ e et al 2009) and implementation in clinics (Belehradek et al 1993;Mir et al 2006;Edhemovic et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Primary manipulation of the target tissue with electroporation, hyperoxygenation, treatment with PDT sensitizers and/or hyperthermia have been shown to increase the effectiveness of PDT [57][58][59][60]. Also, work is being done to increase the depth of penetration for PDT by designing photosensitizers that can be directly activated by infrared or nearinfrared light, wavelengths that can penetrate very deeply into tissue, or by creating constructs that include upconverting nanophosphors that can absorb light in these wavelengths and emit the activating visible light [61][62][63][64][65].…”
Section: Five-year Viewmentioning
confidence: 99%